Paralympic Judo - Pierantozzi, E.; Maussier, N. (The Arts and Sciences of Judo, 2024)
The Paralympic Games (PG), which evolved from the Stoke Mandeville Games, have developed into the world`s second largest multi-sport event, focusing on athletic ability rather than disability. This shift highlights the growing recognition and development of Paralympic sports, including judo. Judo is a Japanise martial art that promotes disci-pline, respect and personal growth. The inclusion of judo in the Paralympic programme has a significant history, with its first appearance at the Seoul Paralympic Games in 1988. The Tokyo 2020 PG and Paris 2024 PG marked significant milestones for judo, with unprecedented participation in Japan and a change in the classification system of Para judoka and consequent changes in their division in competition in France. Until the 2020 PG, Para judoka were classified into three classes based on their visual impairment, however they were fighting together, divided only by gender and weight. Some studies showed that athletes with partial vision tended to outperform athletes who were completely blind in competitive settings. Therefore, after the Tokyo 2020 PG, a new classification system, J1 and J2, was introduced to better differentiate performance levels and ensure a fairer competition. Paralympic judo competitions follow the same rules as Olympic judo, with some adjustments. The physical training guidelines for Para judo are also fundamental for Para athletes, considering their unique psycho-physical needs and the demands of the sport. Participation in sport can improve quality of life significantly for athletes with disabilities, making it a component of their training and rehabilitation programmes. Paralympic judo embodies the principles of judo`s founder Jigoro Kano, who saw judo as a means of per-sonal and social development, promoting self-discipline, respect for others and resilience.